Assessing wear time and perceptions of wearing an ankle foot orthosis in patients with peripheral artery disease. Issue 4 (10th August 2022) - Dinkel, Danae; Hassan, Mahdi; Rech, John P.; DeSpiegelaere, Holly; Johanning, Jason; Pipinos, Iraklis; Myers, Sara
Abstract: Background: Peripheral artery disease (PAD) is a cardiovascular disease that affects walking ability. An ankle foot orthosis (AFO) may improve walking distances in those with PAD. Little research has explored if those with PAD wear a prescribed AFO and their perceptions of wearing the device. Objective: To assess wear time of an AFO and explore perceptions of wearing the device in patients with PAD. Design: Convergent mixed methods. Setting: The study was conducted through a tertiary care medical center, and the research participants used the device in the community. Participants: Thirty‐six patients, all older adult males, were enrolled in this study. Fourteen patients completed the study and 11 supplied sufficient accelerometer data to include in the analysis. Interventions: An AFO was worn for 3 months. An accelerometer was placed on the AFO for 7 days at the midpoint (1.5 months) and endpoint of the intervention (3 months) to assess wear time. Semi‐structured interviews explored patients' perceptions of wearing the AFO. Main Outcome Measure: The primary outcome measure was wear time measured objectively via accelerometer and subjectively via interview. Results: Patients (n = 14) wore the AFO approximately 8 hours/day. Patients reported barriers such as challenges wearing the AFO during daily household activities (using stairs, being on uneven terrain), discomfort, clothing or footwear issues, and driving challenges. Positive effects of wearing the AFO were also reported, primarily the ability to walk further. Conclusions: An AFO may be an acceptable therapeutic intervention to improve perceived walking performance in older adult males with PAD. Addressing participants' perceptions of the AFO and barriers to wear are essential to increasing the positive effect the device has on participants' ambulatory activity.